Multilevel orthopedic surgery for crouch gait in cerebral palsy: An evaluation using functional mobility and energy cost - Ganjwala, Dhiren (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: The evidence for the effectiveness of orthopaedic surgery to correct crouch gait in cerebral diplegic is insufficient. The crouch gait is defined as walking with knee flexion and ankle dorsiflexion through out the stance phase. Severe crouch gait in patients with spastic diplegia causes excessive loading of the patellofemoral joint and may result in anterior knee pain, gait deterioration, and progressive loss of function. We retrospectively evaluated the effect of surgery on the mobility and energy consumption at one year or more with the help of validated scales and scores. MATERIALS AND METHODS: 18 consecutive patients with mean age of 14.6 years with cerebral diplegia with crouched gait were operated for multilevel orthopaedic surgery. Decisions for surgery were made with the observations on gait analysis and physical examination. The surgical intervention consisted of lengthening of short muscle-tendon units, shortening of long muscles and correction of osseous deformities. The paired samples t test was used to compare values of physical examination findings, walking speed and physiological cost index. Two paired sample Wilcoxon signed rank test was used to compare functional walking scales. RESULTS: After surgery, improvements in functional mobility, walking speed and physiological cost index were found. No patient was able to walk 500 meters before surgery while all were able to walk after surgery. The improvements that were noted at one year were maintained at two years. CONCLUSIONS: Multilevel orthopedic surgery for older children and adolescents with crouch gait is effective for improving function and independence.